The Effect of Emotional Intelligence, Work Discipline and Motivation on Employee Performance in Battalion A Pioneer Unit of the Metro Jaya Regional Police Mobile Brigade - Leonard Leonard; Harries Madiistriyatno; Widya Nengsih (Dinasti International Journal of Digital Business Management, 2026)
Employee performance is a crucial factor in supporting the effectiveness of police duties, especially in the A Pioneer Battalion of the Mobile Brigade Unit of the Metro Jaya Regional Police which has operational task characteristics with a high level of risk and work dynamics. Optimal employee performance is greatly influenced by psychological aspects and work behavior, including emotional intelligence, work discipline, and motivation. This study aims to analyze the influence of emotional intelligence, work discipline, and motivation on employee performance, both partially and simultaneously. This study uses a quantitative approach with a survey method. The population in this study amounted to 120 A Pioneer Battalion employees, with a sample of 92 respondents determined using a specific sampling technique. Data were collected through a questionnaire with a Likert scale of 1–5, then analyzed using multiple linear regression methods with the help of the SPSS program version 29. The results of the study indicate that partially emotional intelligence has a positive and significant effect on employee performance with a t-value of 4.697 and a significance level of 0.000. Work discipline also has a positive and significant effect on employee performance with a t-value of 5.045 and a significance level of 0.000. In addition, motivation has a positive and significant effect on employee performance with a t-value of 4.499 and a significance of 0.005. Simultaneously, emotional intelligence, work discipline, and motivation have a significant effect on employee performance with an F-value of 16.866 and a significance of <0.001. The coefficient of determination (R Square) of 0.365 indicates that the three independent variables are able to explain 36.5% of the variation in employee performance, while the rest is influenced by other factors outside the research model. This finding confirms that strengthening emotional intelligence, enforcing work discipline, and increasing motivation in an integrated manner are important strategies in improving the performance of employees of Battalion A Pelopor Satuan Brimob Polda Metro Jaya